PENGARUH ATRIBUT PRODUK TERHADAP PERSEPSI KONSUMEN ATAS PRODUK PASTA GIGI HERBAL HNI-HPAI DI KOTA PADANG - Sri Rahma Yani; Rose Rahmidani (Jurnal Ecogen, 2019)
Abstract : This research  aims to analyze (1) Effect of product brands on consumer perceptions of HNI-HPAI herbal toothpaste products in Padang City, (2) Effect of product quality on consumer perceptions of HNI-HPAI herbal toothpaste products in Padang City, (3) Effect of product packaging on consumer perceptions of HNI-HPAI herbal toothpaste products in Padang City. This type of research is descriptive associative. The sampling technique is convenience sampling with a total sample of 100 people in the city of Padang who use Herbal HNI-HPAI toothpaste in the city of Padang. Data analysis techniques used descriptive analysis and multiple regression analysis using the Statistical Product and Service Solution (SPSS) program. The results showed that (1) the product brand had a positive and significant effect on consumers 'perceptions of HNI-HPAI herbal toothpaste products in Padang City, (2) product quality had a positive and significant effect on consumers' perceptions of HNI-HPAI herbal toothpaste products in the City Padang, (3) product packaging has a positive and significant effect on consumers' perceptions of HNI-HPAI herbal toothpaste products in Padang City. Keywords: consumer perception, product attributes, brand, quality, packaging